Reactive power compensation for a distribution system with distorted system voltages: A new approach/ Mohd Fau'ad Faisal - Faisal, Mohd Fau'ad (2001)
Electrical power will be 'transported' through transmission lines to populated or industrial areas where the voltages will be reduced to the subtransmission voltage levels of 11 kV, 22 kV or 33 kV through step-down power transformers at the main intake substations. The electrical power is then delivered to customers via the underground or overhead distribution systems. The distribution system fed from the distribution transformer stations, supplies power to the domestic or industrial and commercial consumers. Figure 1-1 depicts schematically the structure and components of a typical power system.